Coelomic epithelium-derived cells in visceral morphogenesis - Ariza, Laura; Carmona-Mejías, Rita María; Cañete, Ana; Cano, Elena; Muñoz-Chápuli-Oriol, Ramón (American Association for Anatomy, 2016)
Coelomic cavities of vertebrates are lined by a mesothelium which develops from the lateral plate mesoderm. During development, the coelomic epithelium is a highly active cell layer, which locally is able to supply mesenchymal cells that contribute to the mesodermal elements of many organs and provide signals which are necessary for their development. The relevance of this process of mesenchymal cell supply to the developing organs is becoming clearer because genetic lineage tracing techniques have been developed in recent years. Body wall, heart, liver, lungs, gonads, and gastrointestinal tract are populated by cells derived from the coelomic epithelium which contribute to their connective and vascular tissues, and sometimes to specialized cell types such as the stellate cells of the liver, the Cajal interstitial cells of the gut or the Sertoli cells of the testicle. In this review we collect information about the contribution of coelomic epithelium derived cells to visceral development, their developmental fates and signaling functions. The common features displayed by all these processes suggest that the epithelial–mesenchymal transition of the embryonic coelomic epithelium is an underestimated but key event of vertebrate development, and probably it is shared by all the coelomate metazoans
Keywords: Morfogénesis; Coelomic epithelium; Visceral; Development; Mesothelium